Implementation Of Scientific Integration-Based Teaching (At The Faculty of Science and Technology UIN Alauddin Makassar) - Titi Mildawati (IAIN PAREPARE, 2022)
This research discusses the Implementation of Scientific Integration-Based Teaching at UIN Alauddin Makassar Faculty of Science and Technology. There are several subproblems that will be discussed in this study. First, how is the concept of scientific integration at UIN ALauddin Makassar?. Second, how is the concept of teaching at the Faculty of Science and Technology UIN Alauddin Makassar. Third, the implementation of scientific integration-based teaching at UIN Alauddin Makassar Faculty of Science and Technology. To answer the problem, the study used methods, observations or observations directly, interviewed online by phone and used questionnaires with google form and studied scientific literature related to the discussion of this study. Scientific papers are also systematic, controlled, empirical, and critical investigations of natural phenomena guided by theories about these phenomenological phenomenological approaches as well as one of the approaches used in this study. The rapid development of science in the development of science dichotomy that becomes the separation between religious science and general science that these two sciences should not be separated between the two so that in the development of the transformation of IAIN into UIN that has opened the opportunity for the public to choose more broadly from various public faculties that become an attraction for the community. But on the other hand, public faculties that have been opened by UIN should still pay attention to the image of UIN as an Islamic educational institution. As an Islamic educational institution, UIN must implement integrated teaching between public faculties by incorporating religious content so that the integration of science becomes a characteristic of differentiating with other public campuses.